(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Under the new development pattern featuring domestic circulation as the mainstay and domestic and international circulation reinforcing each other, the influence of digital inclusive finance on residents’ consumption is becoming increasingly prominent. This paper takes 31 provinces (autonomous regions and municipalities directly under the Central Government) in China as the research samples and uses panel data from 2014 to 2023. By constructing a fixed-effect model with STATA software and conducting regression analysis, it empirically explores the impact of digital inclusive finance on the consumption level of residents. The research results show that digital inclusive finance has a significant positive impact on the consumption level of residents. From a dimensional perspective, the impact of digital inclusive finance on the consumption level of residents varies. The impact of coverage breadth is the most significant, while the impact of usage depth is not significant, and the digitalization degree is only significant at the 10% level. Based on this, this paper puts forward corresponding suggestions, with the aim of providing some references for giving full play to the promoting role of digital inclusive finance on residents’ consumption.